Stochastic Forcing of Potential Vorticity: Observations - Egger, Joseph; Hoinka, Klaus-Peter (Journal of the Atmospheric Sciences, 2011)
The linear theory of point correlation maps for synoptic systems relies so far mainly on specifications of stochastic forcing due to nonlinear processes that are not based on observations. Forty-year ECMWF Re- Analysis (ERA-40) data are used to derive time series of the forcing terms in a potential vorticity equation for a correlation point in the North Atlantic storm-track region. It is found that the forcing correlations are restricted to distances less than 1500 km to the correlation point in zonal direction and just a few hundred kilometers in meridional direction. The forcing is not even approximately white in time. Covariances of forcing and potential vorticity are presented as well. An advection equation with simple damping and realistic stochastic forcing is solved to approximate the observed covariances of forcing and potential vorticity.